Why Are There so Many Plant Species That Transiently Flush Young Leaves Red in the Tropics? - Gong, Wei-Chang; Liu, Yan-Hong; Wang, Chuan-Ming; Chen, Ya-Qing; Martin, Konrad; Meng, Ling-Zeng (Frontiers in Plant Science, 2020)
Delayed greening of young leaves is a ubiquitous and visually striking phenomenon in the tropics. Here, we investigated the potential ecological functions of red coloration patterns in young leaves. To detect any protective function of the red coloration on the young leaves, leaf damage by insect herbivores was recorded in the field. To determine capacity for chemical defense, the concentrations of tannins and anthocyanins were measured in both young and mature leaves. To test the hypothesis that anthocyanins function as photo-protective molecules, chlorophyll content, maximum photochemical efficiency of PSII (Fv/Fm), non-photochemical quenching (NPQ), and effective quantum yield of PSII (ΦPSII) were measured in the field. Phylogenetic relationships were analyzed to test the relationary significance of the occurrence of redness in young leaves. Compared to the coloration in non-red leaves, young red leaves had significant higher anthocyanins and tannins content and lower herbivore damages. Young, red leaves had the lowest Fv/Fm values, which were significantly lower than those of non-red leaves. NPQ values in young red leaves were comparable to those of other groups. Although young red leaves had high ΦPSII, these values were significantly lower than those of the other three groups. The results suggest that the red coloration of young leaves protects them from insect herbivory primary by chemical defense through high concentrations of tannins and anthocyanins. Additionally, low Fv/Fm values in young red leaves indicate that anthocyanins might not be functioning as light attenuators to compensate for insufficient photo-protection mediated by NPQ. And finally, red coloration in young leaves is predominantly a result of adaptation to heavy herbivory stress but without significant intrinsic phylogenetic relationship of plant species.